Touch Location Error Analysis of a Low-Cost Piezoresistive Array Sensor - Altun, Kerem; Sarp, Mehmet Oguz (IEEE, 2025)
In this paper, we investigate error characteristics of touch location for a very low-cost piezoresistive array sensor. The act of touch is performed by placing 100 g and 150 g weights on two different sensors designed as 5x5 and 7x7 array formations. Center of pressure calculation is performed two different ways; by using the whole measurement matrix and one of its submatrices. The accuracy and precision of the sensor is reported qualitatively, with a visual representation. It is demonstrated that 7x7 sensor and the submatrix give better results as compared to their alternatives.
Keywords: piezoresistive sensor; touch sensing; error characterization; accuracy and precision; PRESSURE SENSOR; Computer Science; Engineering; Telecommunications